The Impact of Audiobooks on Female Adolescents’ Knowledge and Perceptions of Menstrual Hygiene in Emergencies - Anhar, Vina Yulia; Fakhriyah, Fakhriyah; Noor, Ihya Hazairin; Fitria, Yanti; Noor, Meitria Syahadatina; Putri, Andini Octaviana; Nisa, Mufatihatul Aziza; Yolanda, Zuhrufa Wanna; Chellyadiza, Alfitri; Rahma, Amelia (Lambung Mangkurat, 2024)
Banjar Regency is geographically located in a lowland area crossed by several rivers and hydrographically is greatly influenced by rainfall. From February to March 2023, 17,257 houses in seven sub-districts in Banjar Regency, South Kalimantan were submerged in floods with a height of 20-70 cm. Many women and young women find it difficult to practice Menstrual Hygiene Management (MHM). The use of audiobooks as health promotion media is expected to increase the knowledge and perceptions of young women regarding the practice of MHM when a flood occurs. This study aims to analyze the effect of audiobooks on young women, especially on the variable knowledge and perceptions of MHM in emergency situations. This study is a quasi-experimental study that provides intervention in the form of audiobooks with a one-group pretest-posttest-only design. The sample in this study was 40 female students of Junior High School (SMPN) 2 Martapura Timur, taken using purposive sampling. Data analysis used the T-test with a confidence level of 95%. The results of this study indicate that intervention in the form of audiobooks has proven effective in increasing knowledge (p-value: 0.0001) and perception (p-value: 0.0001) of female adolescents regarding menstrual hygiene management in emergencies. It is expected that the use of audiobooks can be maintained by schools in disseminating information about MHM.